2012
DOI: 10.1086/664745
|View full text |Cite
|
Sign up to set email alerts
|

What Scientific Theories Could Not Be

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. According to the semantic view of scientific theories, theories are classes of models. I show that this view-if taken literally-leads to absurdities. In particular, this view e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
126
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 21 publications
0
126
0
4
Order By: Relevance
“…This criterion is almost exactly the same as the one proposed by Halvorson (2012Halvorson ( , 2015 and Weatherall (2015a). The only difference is that they require the categories of models in question be equivalent, rather than dual.…”
Section: General Relativity and Categorical Dualitymentioning
confidence: 76%
See 2 more Smart Citations
“…This criterion is almost exactly the same as the one proposed by Halvorson (2012Halvorson ( , 2015 and Weatherall (2015a). The only difference is that they require the categories of models in question be equivalent, rather than dual.…”
Section: General Relativity and Categorical Dualitymentioning
confidence: 76%
“…We show that according to a formal criterion for theoretical equivalence recently proposed by Halvorson (2012Halvorson ( , 2015 and Weatherall (2015a), the two are equivalent theories. …”
mentioning
confidence: 75%
See 1 more Smart Citation
“…12 Category theory has recently made its way into the philosophy of science and philosophy of physics literatures as a tool for answering questions about equivalence and the structure of scientific theories. Halvorson (2012Halvorson ( , 2016 and Halvorson and Tsementzis (2017) argue that scientific theories can be represented using the tools of category theory rather than mathematical logic or model theory. Barrett (2017a) and Weatherall (2016aWeatherall ( ,b,c, 2017 argue that the tools of category theory can help us determine when two scientific theories are theoretically equivalent.…”
Section: Limits and Structurementioning
confidence: 99%
“…They underlie Lewis's famous system for counterfactual semantics, modal logic, laws of nature and causation [Lewis, 1973[Lewis, , 1986. More recently, Halvorson [2012] has suggested that similarity is salient for characterizing scientific theories formally: one cannot recover a theory from its models unless one encodes the similarity amongst the models' truth-valuations topologically. And in philosophy of physics, Manchak [2012] has remarked that placing a topology on models of general relativity can describe how different possible relativistic worlds (i.e., relativistic spacetimes) are "nearby" one another.…”
Section: Introductionmentioning
confidence: 99%